Financial Inclusion and Development in the CEMAC - Alter, Adrian (IMF Working Papers; Working Paper ;, 2015)
This paper examines financial inclusion and development in the CEMAC. We explore the level of financial inclusion in the CEMAC through a benchmarking exercise.We construct a measure of financial development gap and analyze its determinants. Using panel data regressions, we find that inflation, income, and natural resources explain most of the financial development level but that better financial sector governance and stronger economic governance are positively associated with financial sector development. Richer and poorer countries can be equally far from their expected financial development levels. Finally, we use a benchmarking exercise to identify countries that have successfully reduced the financial development gap and propose policy measures that CEMAC countries could use to boost financial inclusion.